2004
DOI: 10.1038/emm.2004.10
|View full text |Cite
|
Sign up to set email alerts
|

Acetoaminophen-induced accumulation of 8-oxodeoxyguanosine through reduction of Ogg1 DNA repair enzyme in C6 glioma cells

Abstract: A bstractLarge doses of acetam inophen (APAP) could cause oxidative stress and tissue dam age through production of reactive oxygen/nitrogen (RO S/RNS) species and quinone m etabolites of APAP. Although ROS/RNS are know n to m odify DNA, the effect of APAP on DNA m odifications has not been studied system atically. In this study, w e investigate whether large doses of APAP can m odify the nuclear DNA in C6 gliom a cells used as a m odel system , because these cells contain cytochrom e P450-related enzym es res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 31 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…In addition, certain P450 enzymes such as CYP2E1 and CYP1A2, involved in the APAP metabolism, were degraded after administration of toxic doses of APAP (Snawder et al, 1994;Sinclair et al, 2000), possibly through interaction between these P450 proteins and NAPQI or other reactive metabolites produced from P450-mediated metabolism of APAP. Furthermore, we recently observed that APAP causes degradation of nuclear Ogg1, a DNA repair enzyme, without changing its mRNA level (Wan et al, 2004). By similar mechanisms, p53 may interact directly with NAPQI or other reactive metabolites of APAP (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, certain P450 enzymes such as CYP2E1 and CYP1A2, involved in the APAP metabolism, were degraded after administration of toxic doses of APAP (Snawder et al, 1994;Sinclair et al, 2000), possibly through interaction between these P450 proteins and NAPQI or other reactive metabolites produced from P450-mediated metabolism of APAP. Furthermore, we recently observed that APAP causes degradation of nuclear Ogg1, a DNA repair enzyme, without changing its mRNA level (Wan et al, 2004). By similar mechanisms, p53 may interact directly with NAPQI or other reactive metabolites of APAP (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 94%
“…We previously reported that APAP can cause apoptosis (Bae et al, 2001) and oxidative DNA damage in C6 glioma cells (Wan et al, 2004). Therefore, we hypothesized that the level of p53 would be up-regulated by APAP, similar to the levels observed after exposure to chemotherapeutic agents and other DNA-damaging agents (Vogelstein et al, 2000), because APAP can induce apoptosis (Bae et al, 2001) and wild-type p53 is present in C6 glioma cells (Asai et al, 1994).…”
mentioning
confidence: 80%
“…The deletion and/or mutation through nitroxidative modifications of mitochondrial DNA can exert deleterious effects accompanied with increased amounts of ROS leakage, since mitochondrial DNA encode 13 polypeptides, all of which are subunits of the four mitochondrial ETC proteins [176, 177]. In addition, mitochondrial DNA and proteins are more susceptible to nitroxidative damage due to the absence of protective antioxidant protein catalase, the low activity of DNA repair enzymes, and the absence of histones and polyamines [178]. The damage of mitochondrial DNA, which is essential for normal formation of the ETC components, and inefficient repair are thought to be important in both alcohol- and HFD-induced hepatic cellular damage [179182].…”
Section: Increased Cyp2e1 Levels and The Resultant Nitroxidative Strementioning
confidence: 99%
“…Mitochondrial DNA is also extremely sensitive to nitroxidative damage due to its location within the cell close to the inner mitochondrial membrane, and the relatively low levels of protective antioxidant enzymes, histone proteins, or polyamines and DNA repair enzymes in mitochondria compared to other subcellular organelles including nuclei ([138, 181] and references therein). In addition, it has been suggested that the rate of mutation in mitochondrial DNA is 10-fold higher than that in the nuclear DNA [182].…”
Section: Protein Nitration In Mitochondria and Potential Consequenmentioning
confidence: 99%